Impact of Critical Thinking for Transformative Learning (CTTL) Programme on Elementary Teacher Trainees - Sundar, Shyam; Kumar, Sandip (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Thinking played an important role in human life. All problems and their solution are the result of thinking. The roots of thinking are in the existential reality of which human being on this earth are continuously exploring through various ways. This thinking process occur in oneself and resulting on the basis of one’s belief and value system about self, family and society etc. Observing the need of the society one may get the skill and understanding to make confident oneself. An intervention was carried out on elementary teacher trainees of DIET, Daryaganj through the content which was logical, practicable and universal by the name of ‘Critical Thinking for Transformative Learning’. A pre-test was taken on the perception and belief system on various issues about self, family and society then one year long intervention through the regular conversational classes, Focus group discussion and in morning assembly it was done. After one year long Post-test was administered. The data was collected from the pre and posttest taken in the beginning and last respectively. The data analyses was conducted keeping in mind the objective of the study. A significant behavioral change was observed among the DIET trainees and the logically acceptance of the values system also observed in the study.